2021
DOI: 10.1002/jctb.6940
|View full text |Cite
|
Sign up to set email alerts
|

Pigment production by Scenedesmus dimorphus using different low‐cost and alternative culture media

Abstract: BACKGROUND: This study investigated the feasibility of producing pigments from Scenedesmus dimorphus using different lowcost synthetic and alternative media. Thus the influence of nitrogen and phosphorus deficiency, different nitrogen sources and alternative culture media (wheat bran, garlic powder, wheat bran supplemented with garlic powder) on pigment and biomass production was evaluated. RESULTS: Among the three sources of nitrogen studied (ammonium sulfate, urea and sodium nitrate), urea was the cheapest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The microalgae strains were cultivated in a 2.7 L BG11 medium. 0.3 L of pre-culture was inoculated into the PBR [20]. The room temperature where the microalgae were grown was kept at 25 °C.…”
Section: Cultivation Experimentsmentioning
confidence: 99%
“…The microalgae strains were cultivated in a 2.7 L BG11 medium. 0.3 L of pre-culture was inoculated into the PBR [20]. The room temperature where the microalgae were grown was kept at 25 °C.…”
Section: Cultivation Experimentsmentioning
confidence: 99%
“…dimethyl formamide, sec-butanol, methanol) that allows a rapid and efficient extraction from microalgae with a good stability of pigments (Schumann, Häubner, Klausch, & Karsten, 2005). A range of extraction techniques have been studied to maximize chlorophylls extraction, including MAE extraction for the extraction of chlorophyll a and b in Dunaliella tertiolecta and Cylindrotheca closterium (Ahmad et al, 2022).…”
Section: Chlorophyllsmentioning
confidence: 99%
“…can be employed as mobile phase. Elution gradients (instead of isocratic operation) are preferred for more accurate results (Maroneze et al, 2019;Fernandes et al, 2020;Ahmad et al, 2022). In a recent research, Fernandes et al, revealed that HPLC-PDA with a C30 column can successfully separate different type of chlorophylls when a mixture of methanol:methyl tert-butyl ether:water is used as the mobile phase with a changing gradient (Fernandes et al, 2020).…”
Section: Chlorophyllsmentioning
confidence: 99%
“…e chemical process design is also mainly divided into two stages [14]. e first stage is preliminary preparation.…”
Section: Chemical Process Designmentioning
confidence: 99%